The banks did it : an anatomy of the financial crisis - Fligstein, Neil (Harvard University Press, 2021)
"To understand the 2008 financial crisis, Neil Fligstein looks to the business models of the big US banks. He shows how firms got hooked on mortgages-originating them, securitizing them, selling those securities, and even buying the same securities. In time their addiction nearly collapsed the economy"--